After Abu Ghraib exploring human rights in America and the Middle East - Mokhtari, Shadi 1976- (Cambridge studies in law and society, 2009)
Mokhtari's book examines the changes in the human rights discourse in the United States and the Middle East after the maltreatment and torture of the U.S. captives in the Abu Ghraib and other prisons became public. Through the text analysis of speeches and news reports, as well as in-depth interviews with human rights NGO officials, she makes a thorough assessment that both credits and criticizes the NGOs. Mokhtari shows that human rights advocacy has been successful in pushing the U.S. courts and Congress to recognize the relevance of international human rights law.